Water holding capacity, aggregation, respiration, and chemical character of acid soil amended rice straw biochar enriched with different volumes of liquid extract (sap) of Kappapychus alvarezii - Rembon, Fransiscus Suramas; Kilowasid, Laode Muhammad Harjoni; Afa, La Ode; Rakian, Tresjia Corina; Parapa, Imelia; Laksana, Mohammad Alfi Nanda; Sabaruddin, Laode; Ansi, Azhar; Ramadhan, La Ode Ahmad Nur; Dahlan; Zulfikar (Journal of Degraded and Mining Lands Management, 2024)
The quality of acidic soil is determined by organic C content produced from rice straw biochar in agriculture. In this context, liquid extract from Kappapychus alvarezii (K-sap) is used as a biochar enrichment agent. Therefore, this research aimed to (i) analyze the character of K-sap enriched rice straw biochar with different volumes, as well as (ii) evaluate the impact on soil water holding capacity, size class distribution, aggregate stability index, respiration rate, and acidic soil chemical characters. The treatment tested was the volume of K-sap kg-1 biochar, namely (i) without biochar, (ii) 0 mL, (iii) 500 mL, (iv) 1,000 mL, and (v) 1,500 mL. Each treatment was repeated three times and placed according to a randomized block design procedure. The area covered by K-sap, pore size, and amorphous degree increased while the pore volume of the biochar surface decreased. The addition of 1,000 mL of K-sap kg-1 biochar released a new peak number associated with the aliphatic and aromatic groups. The K-sap enriched biochar increased the proportion of soil aggregate size of 1-2 mm, water holding capacity, carbon storage, pH, total N, available P and K, exchangeable base cations as well as base saturation. Meanwhile, the concentration of Al3+ and H+ were decreased in the acidic soil solution. The results showed that the performance of rice straw biochar, K-sap volumes, soil chemical quality, water holding capacity, and ability to store carbon of the acidic soil was improved by adding K-sap volume.